РЕDАGОGICАL NЕЕD TО DIRЕCTОR STUDЕNTS TО А РRОFЕSSIОN (Scientific journal of the Fergana State University, 2024)
In this article, choosing a profession is a process of self-awareness, the role and importance of the teacher in career guidance, the formation of a creative attitude towards the profession, orientation of students towards a profession based on the requirements of the time, the main aspects of organizing vocational guidance for acquiring a profession, about how young people should prepare, about the need for an individual approach based on the necessary social skills and psychological characteristics of those choosing a profession, about eliminating problems that have arisen regarding morals and morals, education and professional knowledge and skills of youth in the works of sages and thinkers, various opinions on the formation, preparation of school graduates and youth in higher education institutions in the field of vocational education of qualified editors of the West and our country, including the training of specialist editors, improving their professional skills, and the features professional culture and skills of a teacher, psychological aspects of educational activities, reflections on the mental characteristics of the educational process and other problems.